Concrete changes through digital mentoring in elderly care - Kivekäs, Eija; Kinnunen, Ulla-Mari; Ikonen, Johanna; Miettinen, Tanja; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2024)
The responsibility for organizing social and healthcare services has been transferred to the wellbeing services counties. In the change, strong renewal is expected from the counties. Digitalization in services for the elderly has created an opportunity for efficiency, and digital services have improved the possibilities of living at home for the elderly. In the VaDigi -project (Development of digital capacities and approaches in old-aged care), a model was developed to increase healthcare professionals’ digital skills in the services for the elderly. Staff participation in the implementation of the change was strengthened by using reverse mentoring. This study aimed to produce information about the experiences of reverse mentoring. In addition, the possibilities of exploiting reverse mentoring concretized the knowledge of using information systems in a change in work. The target group in this study was professionals working in the elderly care departments in one wellbeing services county. The survey was based on 184 respondents from 14 municipalities. The reverse mentoring reached more than a hundred employees in seven departments. Qualitative analysis was used for group interviews of students (n = 14) and workshop material of units (n = 5). The respondents assessed their knowledge of information systems as good. The competence of digital devices was assessed as weaker. The reverse mentoring produced concrete changes to guarantee departments’ data protection. In addition, mentoring increased the students’ skill in information processing in social and healthcare services. Reverse mentoring as participatory research should be continued.